Multifunctional Gold Nano-Cytosensor With Quick Capture, Electrochemical Detection, and Non-Invasive Release of Circulating Tumor Cells for Early Cancer Treatment - Zhang, Rui; You, Qiannan; Cheng, Mingming; Ge, Mingfeng; Mei, Qian; Yang, Li; Dong, Wen-Fei; Chang, Zhimin (Frontiers in Bioengineering and Biotechnology, 2021)
Circulating tumor cells (CTCs) are metastatic tumor cells that shed into the blood from solid primary tumors, and their existence significantly increases the risk of metastasis and recurrence. The timely discovery and detection of CTCs are of considerable importance for the early diagnosis and treatment of metastasis. However, the low number of CTCs hinders their detection. In the present study, an ultrasensitive electrochemical cytosensor for specific capture, quantitative detection, and noninvasive release of EpCAM-positive tumor cells was developed. The biosensor was manufactured using gold nanoparticles (AuNPs) to modify the electrode. Three types of AuNPs with controllable sizes and conjugated with a targeting molecule of monoclonal anti-EpCAM antibody were used in this study. Electrochemical impedance spectroscopy (EIS) and differential pulse voltammetry (DPV) of the cytosensors were performed to evaluate the cell capture efficiency and performance. The captured 4T1 cells by the AuNPs hindered electron transport efficiency, resulting in increased EIS responses. The cell capture response recorded using EIS or DPV indicated that the optimal AuNPs size should be 17 nm. The cell capture response changed linearly with the concentration range from 8.0 × 10 to 1 × 107 cells/mL, and the limit of detection was 50 cells/mL. After these measurements, glycine-HCl (Gly-HCl) was used as an antibody eluent to destroy the binding between antigen and antibody to release the captured tumor cells without compromising their viability for further clinical research. This protocol realizes rapid detection of CTCs with good stability, acceptable assay precision, significant fabrication reproducibility with a relative standard deviation of 2.09%, and good recovery of cells. Our results indicate that the proposed biosensor is promising for the early monitoring of CTCs and may help customize personalized treatment options.